Spinal Cord Injury: How Could Acupuncture Help? - Qianqian Fan; Omer Cavus; Lize Xiong; Yun Xia (Medical Association of Pharmacopuncture Institute, 2018)
Spinal cord injury (SCI) is one of the most common causes of death and disability worldwide, and it can result in both permanent disability and serial complications in patients. Research shows that patients with SCI complications are often interested in acupuncture for symptomatic relief. Therefore, the issue of physicians advising their patients regarding the use of acupuncture to alleviate SCI complications becomes pertinent. We review and summarize two types of relevant publications: (1) literature concerning acupuncture for SCI and its complications and (2) underlying mechanisms of acupuncture therapy for SCI. Clinical trials and reviews have suggested that acupuncture effectively manages a range of post-SCI complications, including motor and sensory dysfunction, pain, neurogenic bowel and bladder, pressure ulcers, spasticity, and osteoporosis. The effect of acupuncture on post-SCI orthostatic hypotension and sexual dysfunction remains unclear. Decreased oxidative stress, inhibition of inflammation and neuronal apoptosis, regulation of the expression and activity of endogenous biological mediators, and increased regenerative stem cell production are the possible mechanisms of acupuncture therapy for SCI. Although many limitations have been reported in previous studies, given the evidence for the efficacy of acupuncture, we recommend that physicians should support the use of acupuncture therapy for SCI complications. Keywords: acupuncture, complications, review, spinal cord injury